A semilinear problem related to Burgers' equation. Issue 3 (11th February 2023) - Benia, Yassine; Sadallah, Boubaker-Khaled
Abstract : In this work, we study the existence, uniqueness and regularity of the solution to a semilinear Cauchy–Dirichlet problem with variable coefficients, using the Faedo–Galerkin method. We applied this study to a nonhomogeneous Burgers problem considered in a nonparabolic domain. We give a new regularity result of the solution in an anisotropic Sobolev space.